2018
DOI: 10.3390/agronomy8030027
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Management in Aquaponics: Comparison of Three Approaches for Cultivating Lettuce, Mint and Mushroom Herb

Abstract: Abstract:Nutrients that are contained in aquaculture effluent may not supply sufficient levels of nutrients for proper plant development and growth in hydroponics; therefore, they need to be supplemented. To determine the required level of supplementation, three identical aquaponic systems (A, B, and C) and one hydroponic system (D) were stocked with lettuce, mint, and mushroom herbs. The aquaponic systems were stocked with Nile tilapia. System A only received nutrients derived from fish feed; system B receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 46 publications
2
42
2
2
Order By: Relevance
“…Gilthead seabream is one of the most valuable commercial fish species of the Mediterranean, and it has shown very good adaptability to aquaculture [39,40]. The present study showed that the use of brackish water in aquaponics is efficient since the conditioning of the system is associated with the biological filter and achieved by minimizing ammonia and nitrite concentrations and increasing nitrate concentrations.…”
Section: Abiotic Environmentmentioning
confidence: 56%
“…Gilthead seabream is one of the most valuable commercial fish species of the Mediterranean, and it has shown very good adaptability to aquaculture [39,40]. The present study showed that the use of brackish water in aquaponics is efficient since the conditioning of the system is associated with the biological filter and achieved by minimizing ammonia and nitrite concentrations and increasing nitrate concentrations.…”
Section: Abiotic Environmentmentioning
confidence: 56%
“…High nutrient concentrations promote ion toxicity, nutrient imbalance and osmotic stress, and low nutrient concentrations lead to nutrient deficiencies [4]. Lowering the root zone temperature in lettuce reduces the water and nutrient solution absorption [5]. P treatment may control flower stalk anthocyanin synthesis by regulating the epidermal pH value and enzymatic activity [6].…”
Section: Introductionmentioning
confidence: 99%
“…Integration of axial flow with biofilter in a compact vessel in the aquaponics System 1, help this water treatment unit to firstly residue the large particles of fish faeces (source of ammonia) at the bottom of tank and reduce the total amount of ammonia available in the biofilter section (upper part of the vessel) to oxidise into forms of nitrite and nitrate by the nitrifying bacteria. The sediment at the bottom of the water treatment unit will be weekly removed as sludge that can be used as organic fertiliser after treated through composting process or add back to the aquaponics system as plant nutrients after mineralisation proses by the heterotrophic bacteria [13,14]. In addition, similar procedure of sludge removal was applied to the mechanical filter in the System 2.…”
Section: Methodologiesmentioning
confidence: 99%